Improvement of microstructure and initial permeability of Mn0.5Ni0.1Zn0.4GdxFe2-xO4 with sintering temperature - M. Nazrul Islam; Md. Harun-Or-Rashid; Jakiul Islam; Roksana Parvin; A.K.M. Akther Hossain (Results in Physics, 2021)
This article reports the effect of sintering temperatures on microstructure and magnetic properties of Mn0.5Ni0.1Zn0.4GdxFe2-xO4 synthesized by conventional solid state reaction technique and the sintering was performed in the temperature range of 1150 to 1350 °C. The sintered samples were characterized using several techniques. Initial permeability, RQF and magnetic loss factor were measured using impedance spectroscopy. Microstructural analysis and phase identification were analyzed using field emission scanning electron microscope and X-ray diffractometer, respectively. XRD patterns reveal the formation of spinel ferrites phase of all the compositions sintered at 1300 °C, as optimum TS. Average grain size and relative quality factor are found increased with the rise of TS and the highest value of average grain size and RQF are observed for TS = 1300 °C, beyond this temperature average grain size and RQF are found decreased slightly. Magnetic loss factor (tanδ) decreases gradually with the rise of TS. The initial permeability increases with TS and it is found that the value of initial permeability for TS = 1350 °C is more than 5 times higher than that of the value obtained for TS = 1150 °C.